Anastomotic leakage after curative rectal cancer resection has no impact on long-term survival: a propensity score analysis - Ebinger, Sabrina Maria; Warschkow, René; Tarantino, Ignazio; Schmied, Bruno; Marti, Lukas (International journal of colorectal disease, 2015)
PurposeAnastomotic leakage (AL) is a severe and frequent complication of rectal cancer resection, with an incidence rate of approximately 9 %. Although the impact of AL on morbidity and short-term mortality has been established, the literature is contradictory regarding its influence on long-term, cancer-specific survival. The present investigation assessed the long-term survival of 584 patients with stage I-III rectal cancer.MethodsThe 10-year overall survival and cancer-specific survival were analyzed in 584 patients from a single tertiary center. All patients had undergone curative rectal cancer resection between 1991 and 2010. Patients with and without AL were compared using both a multivariate Cox hazards model and propensity score analysis.ResultsA total of 64 patients developed AL (11.0 %, 95 % confidence interval (CI) = 8.7 to 13.8 %). The median follow-up was 5.2 years for all patients; and 7.4 years for patients still alive at the end of the investigated period. AL did persistently not impair cancer-specific survival based on unadjusted Cox regression (hazard ratio of death (HR) = 1.27, 95 % CI = 0.65 to 2.48, P = 0.489); risk-adjusted Cox regression (HR = 1.10, 95 % CI = 0.54 to 2.20, P = 0.799); and propensity score matching (HR = 1.18, 95 % CI = 0.57 to 2.43, P = 0.660).ConclusionsBased on the present propensity score analysis, the oncologic outcomes in patients undergoing curative rectal cancer resections were not impaired by the development of anastomotic leakage.